2010
DOI: 10.1523/jneurosci.4513-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Musical Training Induces Functional Plasticity in Human Hippocampus

Abstract: Training can change the functional and structural organization of the brain, and animal models demonstrate that the hippocampus formation is particularly susceptible to training-related neuroplasticity. In humans, however, direct evidence for functional plasticity of the adult hippocampus induced by training is still missing. Here, we used musicians' brains as a model to test for plastic capabilities of the adult human hippocampus. By using functional magnetic resonance imaging optimized for the investigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
2
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(97 citation statements)
references
References 54 publications
(55 reference statements)
5
85
2
5
Order By: Relevance
“…21,22 In a prospective fMRI study, it was suggested that temporary auditory novelties during music training increase processing in hippocampus and hippocampal effects result from music training. 23 A study didn't find significant differences in auditory number distance test as our study, but it linked abilities in cognitive processing of musicians to auditory skills. 6 It is still not obvious how education types effect improvement of working memory.…”
Section: Discussioncontrasting
confidence: 59%
“…21,22 In a prospective fMRI study, it was suggested that temporary auditory novelties during music training increase processing in hippocampus and hippocampal effects result from music training. 23 A study didn't find significant differences in auditory number distance test as our study, but it linked abilities in cognitive processing of musicians to auditory skills. 6 It is still not obvious how education types effect improvement of working memory.…”
Section: Discussioncontrasting
confidence: 59%
“…The current results suggest that the age at which individuals begins taking lessons (in the current study, age of acquisition was between 2 and 17) is less important than the length of time they are enrolled in lessons. Previous studies support that the number of years an individual is enrolled in lessons greatly affects cognitive functioning (Bailey & Penhume, 2012;Herdener et al, 2010). Inherently, the number of years an individual is in lessons is related to both the age of acquisition and overall education level.…”
Section: Predictors Of Cognition Within Music Trained Eldersmentioning
confidence: 95%
“…More specific structures, including sub-regions of Broca's area (Abdul-Kareem, Stancak, Parkes, & Sluming, 2011;), the corpus callosum (Schlaug, Jäncke, Huang, Staiger, & Steinmetz, 1995), the arcuate fasiculus (AF; Halwani, Loui, Rüber, & Schlaug, 2011), and the hippocampus (Herdener et al, 2010) have been examined for differences between musicians and non-musicians. Abdul-Kareem and colleagues (2011) found increased grey matter volume in male musicians in Broca's area sub-regions responsible for syntactic processing and phonological working memory in language processing but found no differences between the musicians and non-musicians in regions of Broca's area responsible for semantic processing, rhyming, and lexical decision making.…”
Section: Neuroanatomical Differences Between Musicians and Non-musiciansmentioning
confidence: 99%
See 2 more Smart Citations